Arts and Crafts School of Medellín and artisan professionalization. 1869-1901 - Juliana Álvarez Olivares (Historia y Sociedad, 2014)
Historians have long recognized Colombia¿s artisans of the second half of the nineteenth century as a dynamic group who played an active role in the country¿s political movements. However, it was not only their political activism what made this group important during the 1800s. The establishment of technical education centers for the institutionalization and specialization of artisanal occupations caused signi!cant reactions from this social sector. This article analyzes the Arts and Crafts School of Medellin as an institution devoted to the technical and moral education of artisans. Finally, it approaches artisans¿ reactions to the professionalization of their trades and the changes they faced with the arrival of industrialization.